Business environment, human capital structural upgrading, and economic development quality - He, Shengbing; Yao, Huilin (Frontiers in Environmental Science, 2022)
To verify the importance of optimizing the business environment and improving the level of human capital structure to promote economic development, this study employs the panel data of 30 Chinese provinces from the period of 2008 to 2019 and utilizes spatial Dubin model and quantile regression model to analyze the relation between business environment, human capital structure upgrading, and economic development quality. We find that the quality of economic development has a strong spatial correlation and the improvement in business environment promotes human capital structural upgrading and economic development quality. Human capital structural upgrading plays a significant intermediary role, through which improvement in business environment affects economic development quality. Considering the huge differences in the level of economic development in different regions of China, we also conduct a regional heterogeneity analysis. We find the promotion effects of business environment and advanced human capital structure on economic development quality are significant within the sample period, and their promotion effects are significantly heterogeneous and asymmetric across quartiles, indicating that there is heterogeneity in the intensity of dependence of economic development quality on advanced human capital structure and business environment at different stages of economic development. Moreover, by observing the impact trends in the eastern, central and western regions, we find that the impact of business environment and human capital structure on the quality of economic development varies somewhat across provinces. This suggests that the eastern and central regions need to strengthen the optimization of business environment, while the eastern and western regions should pay more attention to the improvement of the level of advanced human capital structure.